2018
DOI: 10.1016/j.comppsych.2018.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating tic-related from non-tic-related impairment in children with persistent tic disorders

Abstract: Children with persistent (chronic) tic disorders (PTDs) experience impairment across multiple domains of functioning, but given high rates of other non-tic-related conditions, it is often difficult to differentiate the extent to which such impairment is related to tics or to other problems. The current study used the Child Tourette's Syndrome Impairment Scale - Parent Report (CTIM-P) to examine parents' attributions of their child's impairment in home, school, and social domains in a sample of 58 children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 37 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…Even when tic symptoms do not impair social, behavioral, or emotional functioning, comorbidities can negatively affect patients’ quality of life more than tics do [ 153 , 165 , 166 ]. Similarly, parents of children with tics reported that non-tic-related symptoms are more problematic than tics themselves [ 167 ]. A large clinical follow-up study of children and adolescents with TS showed an age-related decline in tics, ADHD, and OCD during adolescence, although other symptoms, such as sleep disturbance, remained [ 40 ].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Even when tic symptoms do not impair social, behavioral, or emotional functioning, comorbidities can negatively affect patients’ quality of life more than tics do [ 153 , 165 , 166 ]. Similarly, parents of children with tics reported that non-tic-related symptoms are more problematic than tics themselves [ 167 ]. A large clinical follow-up study of children and adolescents with TS showed an age-related decline in tics, ADHD, and OCD during adolescence, although other symptoms, such as sleep disturbance, remained [ 40 ].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Although a large interview study across nine academic TS and OCD specialty clinics showed a correlation between tic severity and tic impairment 93 , non-tic-related symptoms can be more problematic than tics themselves 94 . Paying attention to comorbid symptoms and treatment is often more important than addressing tics themselves.…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Even when tic symptoms do not impair social, behavioral, or emotional functioning, the comorbidities can negatively affect patients' quality of life more than tics do (Bernard et al 2009;Carter et al 2000;Eddy et al 2011b). Similarly, parents of children with tics reported that non-tic-related symptoms are more problematic than tics themselves (Stiede et al 2018). A large clinical follow-up study of children and adolescents with TS showed an age-related decline in tics, ADHD, and OCD during adolescence, although other symptoms, such as sleep disturbance, remained (Groth et al 2017).…”
Section: Historymentioning
confidence: 99%